Molecular detection and antibiogram of virulent Salmonellae isolated from chicken meat - RAJASHEKHARA, D B; FAIROZE, MD. NADEEM; KARABASANAVAR, NAGAPPA; MADHAVAPRASAD, C B; SHILPA, A G; KOTRESH, A M; BAGALKOTE, PRASHANTH S; NADOOR, PRAKASH (The Indian Journal of Animal Sciences, 2017)
Salmonella has emerged as one of the most common and frequent pathogen associated with the food poisoning. In the present study, a total of 240 chicken meat samples were collected from retail markets of Shivamogga region; where, 13 samples were found positive for Salmonella species by genus specific PCR targeting invA virulent gene, giving an overall prevalence of 5.4%. Retail outlets (slaughter-cum-retailing units) that traditionally processed chicken meat showed higher prevalence of 7.5% (n=120); whereas, retail chicken meat originated from organized abattoirs showed prevalence of 3.3% (n=120). Among traditional retail outlets, those retail units processing multiple animal species showed higher prevalence (8.3%, n=60) of Salmonella spp. compared to those that processed chicken meat alone (6.6%, n=60). All the Salmonella species (n=13) isolated from the chicken meat possessed virulence (invA) gene indicating their potential pathogenic mechanisms and also showed varying degree of susceptibility against common antimicrobials (multiple antibiotic resistance index of 0.1176 to 0.3529). High prevalence rate of Salmonella spp. has important public health concern and underscores a need for intense surveillance and monitoring of retail chicken meat and implementation of food quality assurance systems across the chicken supply chain.